2016
DOI: 10.3928/19404921-20150806-72
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Korean Version of the Perceived Stress Scale-10 (K-PSS-10) in Older Adults

Abstract: The purpose of the current study was to examine the reliability and validity of the Korean version of the Perceived Stress Scale-10 (K-PSS-10). After translation and back-translation of the original PSS-10, a convenience sample of 342 community-dwelling older adults was recruited from senior community centers. Data were analyzed using factor analysis, Pearson's correlation coefficient, and Cronbach's alpha. Using factor analysis with principal axis factoring with oblimin rotation, two factors were extracted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…All participants were split into three age cohorts for purposes of comparison. Given the whole sample was skewed toward the young (M = 31.23, SD = 8.73), the three age cohorts were labeled younger (less than 26 years old), middle (26)(27)(28)(29)(30)(31)(32)(33)(34), and older (35 and above) in this study (a reasonable number was considered in each cohort). All tests of significance were two-tailed, and results were considered significant at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were split into three age cohorts for purposes of comparison. Given the whole sample was skewed toward the young (M = 31.23, SD = 8.73), the three age cohorts were labeled younger (less than 26 years old), middle (26)(27)(28)(29)(30)(31)(32)(33)(34), and older (35 and above) in this study (a reasonable number was considered in each cohort). All tests of significance were two-tailed, and results were considered significant at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the factor structure across studies may be due to the nature of the samples and the statistical approach [10]. The original PSS-4 had a one-factor solution in college samples [15,16], whereas it had a two-factor solution in community samples [17][18][19][20]30] with the exception of Cohen and Williamson's original study, which found a one-factor solution in a community sample [10]. However, Cohen and Williamson used EFA to test the PSS-4's original factor structure [10], and later researchers used CFA to confirm the structure.…”
Section: Discussionmentioning
confidence: 99%
“…The PSS-10 has indeed exhibited strong psychometric properties, possessing good reliability and construct validity among older adults [15,16], multicultural populations [17], and university students [3,11]. Theoretically, the PSS is a unidimensional measure of perceived stress [14], but analyses of the underlying factor structure of the PSS-10 have been generally inconsistent.…”
Section: Pss Factor Structurementioning
confidence: 99%
“…The Korean version of the PSS-10 (K-PSS-10) has been validated and used in a small number of studies on Korean adults [16,24]. However, to date, no research has been conducted on a sample of Korean university students from the ECE profession to provide data about the PSS-10's factorial structure.…”
Section: Pss Factor Structurementioning
confidence: 99%
“…Depression was assessed using the Patient Health Questionnaire-2 (PHQ-2) [ 28 ], and anxiety was assessed using the Generalized Anxiety Disorder, 2-item (GAD-2) questionnaire [ 29 ]. Stress was assessed using the 10-level perceived stress scale [ 30 ]. Other measurements (body weight, BMI, and waist circumference) and laboratory tests (blood sugar levels, blood pressure, and blood lipid levels) were obtained at the participating primary care facilities and performed on only a subset of participating patients as judged necessary by the primary care physicians (64/110, 58.2%).…”
Section: Methodsmentioning
confidence: 99%